2014
DOI: 10.1016/j.jped.2013.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of early amplitude integrated EEG in monitoring term newborns at risk of neurological injury

Abstract: in infants with encephalopathy or other severe illness, aEEG disturbances occur frequently. aEEG provided a better classification of the severity of encephalopathy, detected early subclinical seizures, and allowed for monitoring of the response to treatment. aEEG was a useful tool at the neonatal intensive care unit for predicting poor short-term neurological outcomes for all sick newborn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
2
11
0
1
Order By: Relevance
“…In addition, we found that the incidence of death in the neonatal period in the severely abnormal aEEG group (18/78, 23.1%) was significantly higher than in non‐severely abnormal aEEG group (4/153, 2.6%), which confirms that the severity of aEEG is associated with mortality . In short, early aEEG could predict not only short‐term outcomes but also long‐term outcomes in high‐risk infants …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, we found that the incidence of death in the neonatal period in the severely abnormal aEEG group (18/78, 23.1%) was significantly higher than in non‐severely abnormal aEEG group (4/153, 2.6%), which confirms that the severity of aEEG is associated with mortality . In short, early aEEG could predict not only short‐term outcomes but also long‐term outcomes in high‐risk infants …”
Section: Discussionsupporting
confidence: 91%
“…43 In short, early aEEG could predict not only short-term outcomes but also long-term outcomes in high-risk infants. 44,45 Of the 59 severely abnormal aEEG infants among the 84 infants in the adverse neurological outcome group, 43 (43/59 = 72.9%) infants had severely abnormal amplitude without SWC. In terms of death, CP, epilepsy, and retarded mental or psychomotor developmental, we also found an absence of SWC on aEEG recordings in the majority of infants.…”
Section: Discussionmentioning
confidence: 97%
“… 6 In this field, continuous brain monitoring through aEEG has been used in neonates to assess real-time brain function and for long periods, allowing a better classification of the encephalopathy severity, early detection of subclinical seizures and the monitoring of treatment response. 27 Abnormalities found in the aEEG early in life have strong predictive values of abnormal results at one year of age. 28 …”
Section: Discussionmentioning
confidence: 99%
“…6 Nesse campo, o monitoramento cerebral contínuo por aEEG tem sido aplicado em neonatos para avaliar a função cerebral em tempo real e por longos períodos, o que possibilita uma melhor classificação da gravidade de encefalopatia, a detecção de convulsões subclínicas precoces e o monitoramento da resposta ao tratamento. 27 Anormalidades encontradas no aEEG no início da vida têm fortes índices preditivos de resultados anormais com um ano. 28 …”
Section: Discussionunclassified
“…The initiation of hypothermia to babies with HIE who have moderate to severe abnormal aEEG patterns within the first 6 hours after birth positively affects the neurological outcomes. In a study which comparedcooled infants with non-cooled infants the positive predictive value of aEEG was low (64-75%) within 6 hoursafter birth; but it reached to 80% in both groups within 24-36 hours after birth [34] . In another study, it was reported that possibility of severe neurological damage was high (>80%) in patients having severe suppression in aEEG in the first 48 hours of life [35] .…”
Section: Effects Of Hypothermia On Aeeg Tracesmentioning
confidence: 94%